2013 4th International Conference on Computer and Communication Technology (ICCCT) 2013
DOI: 10.1109/iccct.2013.6749615
|View full text |Cite
|
Sign up to set email alerts
|

Rule based stemmer in Urdu

Abstract: Urdu is a combination of several languages like Arabic, Hindi, English, Turkish, Sanskrit etc. It has a complex and rich morphology. This is the reason why not much work has been done in Urdu language processing. Stemming is used to convert a word into its respective root form. In stemming, we separate the suffix and prefix from the word. It is useful in search engines, natural language processing and word processing, spell checkers, word parsing, word frequency and count studies. This paper presents a rule ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Stemming helps in improving the IR performance especially in terms of recall (Pandey and Siddiqui 2009). Gupta et al (2013) shown the effectiveness of rule-based Urdu stemmer for IR task. 119 rules are made for 2000 words dataset and 86.5 % accuracy is achieved.…”
Section: Information Retrieval (Ir)mentioning
confidence: 98%
See 1 more Smart Citation
“…Stemming helps in improving the IR performance especially in terms of recall (Pandey and Siddiqui 2009). Gupta et al (2013) shown the effectiveness of rule-based Urdu stemmer for IR task. 119 rules are made for 2000 words dataset and 86.5 % accuracy is achieved.…”
Section: Information Retrieval (Ir)mentioning
confidence: 98%
“…Data in these corpora are organized in the form of verbs, nouns, adjectives, punctuations, numbers, special symbols etc. Gupta et al (2013) developed a rule base Urdu stemmer and evaluated its performance on IR task. They tested their proposed Urdu stemmer on 2000 words.…”
Section: Stemmingmentioning
confidence: 99%
“…He established and implemented rules for this purpose to eliminate the suffix and prefix from the inflected words of Urdu. In addition the rule based stemmer for the Urdu language was created by Gupta [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Joshi et al [19] further developed a technique to using machine learning in evaluating MT engines. Tyagi et al [20] [21] developed an approach of translating complex English sentences by first simplifying them and then translating into Hindi. Yogi et al [22] developed an approach to identify candidate translation which are good for post editing.…”
Section: Literature Reviewmentioning
confidence: 99%